Büyük Yatırım Analizlerinde Yeni Genel Bir Yöntem Ve Tersane - Liman Yatırımında Bir Uygulama - Saraçoğlu, Burak Ömer (Fen Bilimleri Enstitüsü, 2009)
Bu araştırma genel olarak büyük yatırımların gerektiği sektörlerde yatırım analizleri problemlerine çözüm olmayı amaçlayan ilgi çekici ender çalışmalardan biri olarak karşımıza çıkmaktadır. Karar verme, yönetim sistemleri, yatırım analizleri, matematiksel ve istatistiksel yöntemler ve yazılım-kodlama literatür taraması çalışmasının gerçekleştirilebilmesi için bir taksonomik çalışma yapılmıştır. Endüstri uygulamaları ve özellikleri kısmında ise bir vaka çalışması yapılacak olan gemi inşaatı sektörü ve liman yönetimi hakkında detaylı bilgi literatür taraması ile sunulmuştur. Yönetim sistemleri taksonomik çalışmasında 70 makale ve kitap taranmıştır. Kaynaklardan en eskisi 1969 yılı en yenisi 2006 yılı baskılıdır. Bu çalışma bir üst yönetim destek sisteminin temellerinin atılmasınına olanak verecektir. Karar verme taksonomik çalışmasında 70 makale ve kitap taranmıştır. En eski kaynak 1973 yılı en yeni kaynak 2006 yılı baskılıdır. Bu çalışmada Analitik Ağ Yönteminin kullanılmasına karar verilmiştir. Yatırım analizleri taksonomik çalışmasında 40 makale ve kitap detaylı şekilde taranmıştır. En eski kaynak 1988 yılında en yeni kaynak 2007 yılında yayınlanmıştır. Bu kaynaklara dayalı olarak çeşitli performans göstergeleri açıklanmış ve sunulmuştur. Matematiksel ve istatistiksel yöntemler taksonomik çalışmasında 70 makale ve kitap irdelenmiştir. Bu kaynaklardan en eskisi 1970 en yenisi 2008 yılında yayınlanmıştır. Yazılım ve kodlama taksonomik çalışmasında 40 makale ve kitap detaylı olarak incelenmiştir. Bu kaynaklardan en eskisi 1986 yılında en yenisi 2007 yılında yayınlanmıştır. Endüstri uygulamaları ve özellikleri başlığı altında gemi inşaatı sektöründe ve liman yönetiminde bulunan ana oyuncular hakkında detaylı bilgiler sunulmuştur. Bu çalışmaların en eskisi 2005 yılında en yenisi 2008 yılında yayımlanmıştır. Bu çalışma ile çok amaçlı karar verme optimizasyonuna ve bulanık mantık temelli çok seçimli karar verme yöntemlerine dayalı yeni genel bir yöntem, yatırım analizlerinde kullanılabilmesi için sunulmuştur. Sunulan yöntem üç ana fazdan oluşmaktadır. Bunlardan birincisi ön karar verme aşaması olup 15 adımdan oluşmakta ve yatırım karar modelinin tanımlama ve araştırma kısımlarını kapsamaktadır. İkinci aşama ise 31 ana adımdan oluşmakta ve yatırım bilgilerinin toplanması ve modelin çalışmasını içinde barındırmaktadır. Son aşama ise 5 ana adımdan oluşmakta ve değerlendirmeler ile sonuçları içinde barındırmaktadır. Bu çalışmada Gelibolu Gemi Endustrisi Sanayi ve Ticaret A.S. ve sanal liman – bakım onarım tersanesi PORREP yatırım analizleri vaka çalışması olarak gerçekleştirilmiştir. Sonuç bölümünde, bu çalışmaya dayalı olabilecek gelecek çalışmalar hakkında bilgi verilmiştir.

This research might be one of the most impressive “cross-industry study” which is devoted to solve basically the decision making problems at investment analysis in shipbuilding industry, logistics industry (port investment), shipping industry, energy sector and other mega investment based industries. A taxonomic study was conducted for the literature review of decision making, management systems, investment analysis, mathematical and statistical methods and software and coding. A literature review was performed in industry applications and properties to give detail information about the industry that the case study would be conducted. In management systems taxonomic study, seventy papers and books were in detail studied. The oldest study was published in 1969 and the newest was published in 2006. This research was probably the first and necessary step in the process of developing an Executive Support System which was in strategic level system of organizations for making the decision at investment analysis in mega investment based industries. In decision making taxonomic study, seventy papers and books were in detail studied. The oldest study was published in 1973 and the newest was published in 2006. In current study, a method based on Analytical Network Process Method was selected for application in the decision making of the investment analysis. In investment analysis taxonomic study, forty papers and books were in detail studied. The oldest study was published in 1988 and the newest was published in 2007. The performance measures were in detail explained and presented. In mathematical and statistical methods taxonomic study, seventy papers and books were in detail studied. The oldest study was published in 1970 and the newest was published in 2008. In software and coding taxonomic study, fourty papers and books were in detail studied. The oldest study was published in 1986 and the newest was published in 2007. In industry applications and properties subtitle, sufficient number of studies were in detail studied to explain the major players and their status in shipbuilding industry and other industries. The oldest study was published in 2005 and the newest was published in 2008. A new generic method for large investment analysis in industry based on multiobjective optimization and fuzzy multi attribute decision making is explained. The proposed method has three main phases respectively named as pre-decision phase that has 15 main steps, in which definition and description of investment decision phase model is executed; decision phase that has 31 main steps in which collection and analyze of investment decision is executed and post-decision phase that has 5 main steps in which analyze and conclusion. A case study to demonstrate that the proposed method can be applied to real world investment decisions in shipbuilding industry and logistics industry (port investment) which is characterized as mega-project and mega-investment industry was conducted in the feasibility evaluation of Gelibolu Gemi Endustrisi Sanayi ve Ticaret A.S. that is the name of a legal entity of a shipyard in Turkey and a virtual feasibility evaluation of a virtual entity of port and ship repair yard named as Virtual Gelibolu PORREP. This thesis and research also concludes by highlighting future directions for research in several industries and in different research areas based on this area.
A New Generic Method For Large Investment Analysis In Industry And An Application In Shipyard - Port Investment
Tez (Doktora) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2009
Thesis (PhD) -- İstanbul Technical University, Institute of Science and Technology, 2009
Keywords: Karar verme; yönetim sistemleri; yatırım analizleri; matematiksel ve istatistiksel yöntemler; gemi inşaatı; lojistik; bulanık mantık; Pareto optimum; üst yönetim destek sisteminin; Decision making; management systems; investment analysis; mathematical and statistical methods; shipbuilding; logistics; fuzzy logic; Pareto optimal; executive support systems